Risk Prediction for Niemann-Pick Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
A retrospective chart review of 216 patients with Niemann-Pick disease type C (NP-C) was conducted in 5 centers in Europe including University of Amsterdam and 2 in Australia.